2020
DOI: 10.1016/j.ajo.2020.03.006
|View full text |Cite|
|
Sign up to set email alerts
|

Ratio of Axial Length to Corneal Radius in Japanese Patients and Accuracy of Intraocular Lens Power Calculation Based on Biometric Data

Abstract: MIKI KAMIKAWATOKO OMOTO, HIDEMASA TORII, KEN HAYASHI, MASAHIKO AYAKI, KAZUO TSUBOTA, AND KAZUNO NEGISHI PURPOSE: To evaluate the features of the axial lengthto-corneal radius (AL/CR) ratio in Japanese patients with cataracts and to determine the accuracy of intraocular lens (IOL) power calculation formulas according to the AL/CR features and the axial length (AL).DESIGN: Retrospective observational case series. METHODS: Setting was a clinical practice. Patient population was a total of 1,135 eyes (1,135 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…The prevalence of myopia is growing, especially in Asia [ 3 , 4 , 5 ]. While many methods are being used to overcome this issue [ 6 , 7 , 8 , 9 , 10 , 11 ], the challenge still remains.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of myopia is growing, especially in Asia [ 3 , 4 , 5 ]. While many methods are being used to overcome this issue [ 6 , 7 , 8 , 9 , 10 , 11 ], the challenge still remains.…”
Section: Introductionmentioning
confidence: 99%
“…For eyes with short AL, the accuracy between the formulas is altered depending on the anterior chamber depth (ACD) because the change in effective lens position (ELP) has an increased effect on IOL power (Eom et al 2014). A recent study reported that the IOL power calculation formula selected by the ratio of AL and K was evaluated to be more accurate than that by AL subgroup alone (Omoto et al 2020). Melles et al (2018) explored 13 301 eyes and reported the tendency of refractive prediction error in the diversity of IOL power calculation formulas according to K, ACD and AL.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that the IOL power calculation formula selected by the ratio of AL and K was evaluated to be more accurate than that by AL subgroup alone (Omoto et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This index is also important at older ages, as recent studies have shown that using the axial length/ corneal radius of curvature ratio can be very useful to determine the optimal intraocular power in patients with cataracts. 32 One of the interesting findings of the present study was the relationship between anterior chamber depth and refractive errors. In most previous studies, an inverse relationship was found between anterior chamber depth and spherical equivalent.…”
Section: Discussionmentioning
confidence: 66%
“…In other words, in two individuals with the same axial length/corneal radius of curvature ratio, the refraction differences can be attributed to the crystalline lens thickness as well as the contribution of the anterior chamber depth and vitreous chamber depth. This index is also important at older ages, as recent studies have shown that using the axial length/corneal radius of curvature ratio can be very useful to determine the optimal intraocular power in patients with cataracts 32 …”
Section: Discussionmentioning
confidence: 99%